COVID-19 Seroprevalence in a Mixed Cohort of SARS-CoV-2 PCR Positive and Exposed Subjects - Knowles, Giles; Winkie, Colin; Umer, Amna; Moffett, Kathryn; Weisse, Martin; Gupta, Shipra (COVID, 2023)
Early in the SARS-CoV-2 pandemic, polymerase chain reaction (PCR) testing was reserved for symptomatic patients. However, many infections were asymptomatic or mildly symptomatic. Positive serologic antibody (Ab) testing is theorized to be a marker of prior infection, allowing for identification of the true burden of the disease and the establishment of links between outbreaks. The objective was to assess serologic testing in subjects after PCR testing and compare seropositivity rates of household vs. non-household close contacts. We identified subjects who were PCR-positive between March 2020 and May 2021. Index cases and close contacts then underwent serologic testing for IgG against the SARS-CoV-2 nucleocapsid N-protein. One hundred and thirteen subjects underwent serologic testing with a sensitivity of 65.0%, specificity of 78.9%, positive predictive value of 92.9%, and negative predictive value of 34.9%. Index cases comprised 20.5% of subjects, and 73.9% were seropositive (p = 0.01). Close contacts included 72% household contacts and 28% non-household contacts. One seropositive case had no prior PCR and four were PCR negative. No statistical difference existed in seropositivity between household and non-household contact (53.1% vs. 43.8%, p = 0.4). Testing for IgG against SARS-CoV-2 N-protein may identify previously unrecognized infections in the community. Seropositivity rates of household vs. non-household contacts were not significantly different, and >50% of household contacts were seropositive.